2021
DOI: 10.3390/ijms22062906
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Arabidopsis: BBX Regulators in Crop Plants

Abstract: B-box proteins represent diverse zinc finger transcription factors and regulators forming large families in various plants. A unique domain structure defines them—besides the highly conserved B-box domains, some B-box (BBX) proteins also possess CCT domain and VP motif. Based on the presence of these specific domains, they are mostly classified into five structural groups. The particular members widely differ in structure and fulfill distinct functions in regulating plant growth and development, including seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 106 publications
1
32
0
Order By: Relevance
“… Scheme illustrating major features of BBX proteins in each structure group (Modified from Talar et al [ 11 ]). …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… Scheme illustrating major features of BBX proteins in each structure group (Modified from Talar et al [ 11 ]). …”
Section: Figurementioning
confidence: 99%
“…In tomato, rice, apple, and grapevine, some stress-and hormone signaling-related cis-elements, such as the LTR, MBS, HSE, ABA-responsive element (ABRE), ethylene-responsive element (ERE), and gibberellin-responsive element (GARE), have been detected in the promoter region of most BBX genes, implying these genes are involved in hormone signaling pathways and abiotic stress responses [8,[31][32][33] Figure 1. Scheme illustrating major features of BBX proteins in each structure group (Modified from Talar et al [11]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the biological significance of these family expansion events for the flowering regulation mechanism of strawberry need to be further explored, since functional studies of the above genes in plant flowering regulation remain scarce. BBX genes are reported to play diverse functional roles in plant biological processes [4]. Increasing evidence has demonstrated that BBXs show special gene expression patterns related to their function.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous analyses concerning the biological functions of AtBBXs have been reported. The biological functions of AtBBXs are associated with multiple physiological and biochemical processes, including developmental regulation, flowering time regulation, and response to external stress [2,4]. AtBBX28 is a negative regulator of AtHY5 that participates in the COP1-HY5 pathway mediating photomorphogenic development via a physical interaction with the AtHY5 protein, which represses the activity of AtHY5 in a dose-dependent manner in Arabidopsis [5].…”
Section: Introductionmentioning
confidence: 99%
“…The BBX gene family, encoding zinc-finger proteins, is an important family of transcription factors in plants, with functions including response to environmental changes, and plant growth and development [ 13 , 14 ]. BBX proteins generally have one or two B-box domains, and some members also have VP domains and CCT domains [ 15 ]. In plants, the B-box domain contains approximately 40 amino acids and is highly conserved, but there are still some differences among different B-box motifs [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%